DIVESTASI SAHAM PERTAMBANGAN PADA KONTRAK KARYA ANTARA PEMERINTAH REPUBLIK INDONESIA DENGAN PT. NEWMONT NUSA TENGGARA - ADI SYAFRIZAL SIREGAR (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Jelly Leviza, SH, MHum Stock divestment is taking over some stocks of foreign investment to the other party, done either directly or by an auction in order to improve social welfare. The objectives of the research are to analyze the divestment agreement made in a contract of work between the Government of the Republic of Indonesia and PT. Newmont Nusa Tenggara based on the perspective of the prevailing laws and regulations in Indonesia, to analyze the mechanism of stock divestment that has to be done by PT. Newmont Nusa Tenggara as stated in the content of the work contract with the Government of Indonesia, and to analyze the legal consequences of the default done by PT. Newmont Nusa Tenggara that does not divest their stocks in accordance with what is mandated in the Law No. 4/2009 on Mineral and Coal Mining.This is a normative juridical research with analytical descriptive approach. The main data are sourced from secondary data collected by conducting library research. They are collected through document study, and are analyzed qualitatively.The results of the research demonstrate that the agreement made concerning stock divestment in the work contract is made in the provisions in Article 112 of the Law No. 4/2009 and Article 24 concerning national benefit promotion, particularly Article 24 Paragraph (4) of the contract content. The mechanism of the stock divestment that has to be undergone by PT. Newmont Nusa Tenggara is stipulated in the Regulation of the Minister of Energy and Human Resources No. 27/2013 on Procedures and Determination of Stock Divestment Price, and Investment Changes in Mineral and Coal Mining Companies. The legal consequences for the default done by PT. Newmont Nusa Tenggara for not divesting its stocks is that Government of the Republic of Indonesia shall file a lawsuit to International Arbitrary and issue four final decisions winning the lawsuit filed by Government of the Republic of Indonesia concerning the dispute over divestment.Keywords: Stock Divestment, Mining Company, Work Contract.